Reversal of rocuronium‐induced intense neuromuscular blockade by sugammadex in Korean children: A pharmacokinetic and pharmacodynamic analysis - Sang‐Hwan Ji; Ki Young Huh; Jaeseong Oh; Hee‐Jeong Jeong; Young‐Eun Jang; Eun‐Hee Kim; Ji‐Hyun Lee; Jin‐Tae Kim; Hee‐Soo Kim (Wiley, 2023)
Abstract Sugammadex, a selective antagonist of steroidal non‐depolarizing neuromuscular blocking agents, has been used in children in limited circumstances. However, neither pharmacokinetics (PKs) nor recovery profile of sugammadex for intense neuromuscular blockade reversal in children have been reported. This prospective study aimed to obtain a PK model of sugammadex and evaluate its efficacy and safety for intense neuromuscular blockade reversal in children. Forty children (age, 2-17 years) who underwent surgery that required early neuromuscular blockade reversal were enrolled. After neuromuscular blockade with 1 mg∙kg−1 of rocuronium, sugammadex (2, 4, and 8 mg∙kg−1) or a conventional dose of neostigmine (0.03 mg∙kg−1) was administered randomly after confirmation of zero post‐tetanic count. The plasma concentrations of rocuronium and sugammadex were measured 2 min after rocuronium injection; immediately before, 2, 5, 15, 60, 120, 240, and 480 min after the study drug injection. Response to train‐of‐four stimulation was continuously recorded. Noncompartmental analysis and population PK modeling were performed. For pharmacodynamics, the recovery profile was measured. Three‐compartment PK model was established for sugammadex. The median (interquartile range [IQR]) time from injection of 8 mg∙kg−1 of sugammadex to recovery of T4/T1greater than or equal to 0.9 at train‐of‐four stimulation was 1.1 (IQR: 0.88-1.8) min. No adverse events related to sugammadex were observed. We present a PK analysis of sugammadex for rocuronium‐induced intense neuromuscular blockade reversal in children with its recovery profile. The time to recover T4/T1 greater than or equal to 0.9 at train‐of‐four stimulation with 8 mg∙kg−1 of sugammadex was less than 3 min and comparable to that in adults.